Post-implementation knowledge retention of stroke: the lasting influence of FAST Heroes - Emilia Orologa; Maria Baskini; Kalliopi Tsakpounidou; Christos Keramydas; Hariklia Proios; Hariklia Proios (Frontiers Media S.A., 2024)
BackgroundFAST Heroes is a kindergarten-based educational program that teaches young children and their extended families (parents, grandparents), the main stroke symptoms (Face, Arm, and Speech), and the timely and appropriate steps in the event of a suspected stroke (Time). However, post-campaign knowledge retention remains a challenge.AimsThe purpose of the current study was to investigate whether and to what extent grandparents' stroke knowledge is maintained 44 months after the initial implementation of the program.MethodsForty-five participants engaged in the present study (35 women, 10 men; 72.8§5.3) and completed an adapted version of the FAST Heroes Stroke Preparedness Questionnaire via phone calls.ResultsCompared to immediately post-program implementation, respondents were still able to recall arm weakness (OR = 1.63; p = 0.246) and slurred speech (OR = 2.02; p = 0.075) as main stroke symptoms. A decrease was observed in recalling facial drooping (OR = 0.44; p = 0.042). Reporting of the appropriate course of action, was found to be increased (OR = 4.17; p < 0.001). Respondents remembered the emergency number to call, i.e., 112 (OR = 0.97; p = 0.947).ConclusionThe results showed that awareness regarding the common signs of a stroke and the importance of promptly contacting emergency services following a stroke, in the population group mostly affected by stroke, is retained. Exploring knowledge preservation in a greater sample size is warranted.